Learning Vocabulary Using 2D Pictures is More Effective than Using Immersive 3D Stereoscopic Pictures. Issue 4 (25th February 2022) - Kaplan-Rakowski, Regina; Lin, Lin; Wojdynski, Tomasz
ABSTRACT: This experimental study investigated the effect of immersive stereoscopic three-dimensional (S3D) pictures on productive and receptive vocabulary recall. The inherent perception of depth in S3D pictures facilitates learners' immersion, making those pictures a potentially effective learning aid. The results of paired t -tests of this within-subjects study ( N = 371) revealed that S3D pictures were associated with significantly lower scores on vocabulary recall than two-dimensional pictures (2D). Multivariate regression analysis provided us with two additional findings. First, ownership of S3D equipment was positively associated with performance on S3D images. Second, higher self-reported engagement for 2D images was associated with better learning with 2D images. We suspect that the immersive nature of S3D pictures may have distracted the learners from focusing on the vocabulary learning task or taken away cognitive resources that could have been used for learning. These findings have implications for instruction in immersive spaces, including in virtual, augmented, and mixed reality-based learning environments.